Vegetable Insecticide as an Environmentally Friendly Alternative to Control Crocidolomia pavonana F. on Pak Choi Plants - Djamilah, Djamilah; Fauzi, Ariffatchur; Ginting , Sempurna; Sutrawati , Mimi (Badan Penerbitan Fakultas Pertanian (BPFP), 2025)
Pak choi plant (Brassica rapa L) is a type of vegetable that is popular and loved by the public. This cultivation cannot be separated from pest attacks. Crocidolomia pavonana F. (crop caterpillar) is an important pest that causes severe damage to Pak choi plants. Pest control with the application of synthetic chemical insecticides causes resistance to crop caterpillars, kills natural enemies of insect pests and hurts the environment and human health. Another environmentally friendly alternative for controlling C. pavonana is needed. It is necessary to use vegetable insecticides. Jengkol skin and kabau skin have the potential as plant-based insecticides to control C. pavonana. This research aims to find concentrations of jengkol and kabau skin extracts (vegetable insecticides) that are effective in preventing C. pavonana on Pak choi plants. This research used a Completely Randomized Design (CRD). It was carried out in two stages, namely testing the effectiveness of jengkol and kabau skin extracts on C. pavonana in the laboratory. Laboratory tests were carried out with three treatments of jengkol and kabau skin extract concentrations at concentrations of 4%, 6% and 8% respectively, repeated five times. Observations were carried out for a week. The variable observed was larval mortality. The laboratory test research results showed that 66% mortality occurred in kabau skin extract at a concentration of 8%, and in jengkol skin extract at a concentration of 8%, causing 53% mortality of crop caterpillar larvae.